ANALISIS CONTENT MARKETING DAN ELECTRONIC WORD OF MOUTH (E-WOM ) TERHADAP KEPUTUSAN PEMBELIAN GENERASI Z PADA MEDIA SOSIAL TIK-TOK (STUDI KASUS GENERASI Z KABUPATEN DHARMASRAYA) - Mayroza Wiska; Fenisi Resty; Hidayatul Fitriani Hidayatul Fitriani (MANAJEMEN DEWANTARA, 2022)
The rapid development of technology makes social media one of the most effective marketing strategies to influence purchasing decisions. Moreover, during the current COVID-19 pandemic, various policies have been implemented to minimize the spread of the virus, which has led many companies to start looking at tik-tok as a platform for marketing their products. Because tik-tok is a social media platform that has just emerged and is very popular during the pandemic, it occupies the fourth position as the most widely used social media platform, where most of its users are from Generation Z. Seeing this phenomenon, this research was conducted to find out and analyze what kind of impact is caused by content marketing and electronic word of mouth (e-WOM) on the purchasing decisions of Generation Z on tik-tok social media in Dharmasraya Regency. The purpose of this study was to determine and analyze "the effect of content marketing and electronic word of mouth (e-WOM) on the purchasing decisions of Generation Z cosmetics on tik-tok social media (a case study of Dharmasraya Regency). This study used a quantitative method of collecting data using a questionnaire. The total number of respondents who were used as samples was 225. The results of this study indicate that content marketing and electronic word of mouth (e-WOM) are partially and simultaneously proven to have a significant effect on purchasing decisions. Its R square value is 0.566, which means that all independent variables can explain 56.6% of the dependent variable. while the remaining 43.4% can be explained by other factors not tested in this study.